2011
DOI: 10.4021/cr78w
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Atherectomy and Stent Implantation for Calcified Left Main Lesions

Abstract: BackgroundLeft main coronary artery (LMCA) bifurcation and heavily calcified lesions are common and challenging to treat percutaneously. Rotational atherectomy (RA) may be beneficial in this setting to facilitate stent placement though direct supporting evidence is lacking. This study sought to analyze patients who underwent RA of the LMCA.MethodsConsecutive cases involving RA of the LMCA between 1/1/2004 and 12/31/2009 at a private, tertiary referral hospital were reviewed retrospectively. Medical records, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The optimal BtAR remains unidentified, however the current guidelines recommend the burr size of < 0.7 [ 1 ] or < 0.6 [ 2 ] of the vessel diameter. Recently published studies reflecting implementation of recommendations into clinical practice reported the BtAR < 0.6 [ 3 , 19 , 20 ] or even < 0.5 [ 21 , 22 ] for the overall study population. The mean BtAR (SD) calculated for all patients in the present study was 0.50 (0.12).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal BtAR remains unidentified, however the current guidelines recommend the burr size of < 0.7 [ 1 ] or < 0.6 [ 2 ] of the vessel diameter. Recently published studies reflecting implementation of recommendations into clinical practice reported the BtAR < 0.6 [ 3 , 19 , 20 ] or even < 0.5 [ 21 , 22 ] for the overall study population. The mean BtAR (SD) calculated for all patients in the present study was 0.50 (0.12).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of LMT-RA to the total number of LMT PCIs and to the total number of RA varies among studies from 8.9% to 11.3% and from 6% to 9.3%, respectively [ 46 54 ]. The previously published experience with RA in LMT is summarized in Tables 3 , 4 .…”
Section: Patients and Lesions Treated With Ra In The Current Practicementioning
confidence: 99%